Diagnostic value of multiple projection angle X-ray and CT 3D reconstruction for long-term unreduced posterior hip dislocation - Liu, Yansong; Ma, Yongbo; Liu, Zeming; Ding, Xuzhuang; Yao, Xiaowei; Chang, Jiangqi; Li, Hao; Wu, Tao (Frontiers in Surgery, 2025)
BackgroundLong-term unreduced posterior hip dislocation is a rare and diagnostically challenging condition, with imaging findings often indistinguishable from those of other end-stage hip diseases. It remains a great challenge to determine whether certain imaging characteristics can improve the clinical diagnosis rate of long-term unreduced posterior hip dislocation.MethodsWe retrospectively reviewed 24 patients from 2010 to 2022. The diagnostic values of multiple projection angle X-ray and CT 3D reconstruction for long-term unreduced posterior hip dislocation were evaluated.ResultsFor aureole sign, 45.83% of patients (sensitivity = 45.83%, specificity = 81.52%, accuracy = 78.67%, Youden's index = 0.274, positive predictive value (PPV) = 17.74%, negative predictive value (NPV) = 94.54%, intraobserver consistency = 0.930, and interobserver consistency = 0.903) were diagnosed correctly. For obturator oblique radiograph of the pelvis, 58.33% of patients (sensitivity = 58.33%, specificity = 82.25%, accuracy = 80.33%, Youden's index = 0.406, PPV = 22.22%, NPV = 95.78%, intraobserver consistency = 0.923, and interobserver consistency = 0.900) were diagnosed correctly. For rhombus sign, 70.83% of patients (sensitivity = 70.83%, specificity = 90.94%, accuracy = 89.33%, Youden's index = 0.618, PPV = 40.48%, NPV = 97.29%, intraobserver consistency = 0.943, and interobserver consistency = 0.900) were diagnosed correctly. For CT 3D reconstruction, axial CT (sensitivity = 70.83%), coronal multiplanar reconstruction (sensitivity = 58.33%), and sagittal multiplanar reconstruction (sensitivity = 54.17%), all had high diagnostic values.ConclusionsThe signs, projection angle X-ray, and CT 3D reconstruction identified in this study are valuable in improving the diagnosis for long-term unreduced posterior hip dislocation.